Retinal nerve fiber layer thickness in patients with essential tremor and Parkinson’s disease - Fidancı, Halit; Öksüz, Nevra; Özal, Şeyda; Adıgüzel, Ufuk; Kaleağası, Şükrü; Doğu, Okan (Journal of Surgery and Medicine, 2019)
Aim: Essential tremor (ET) and Parkinson’s disease (PD) are common movement disorders. In PD, visual problems such as impaired color vision and decreased visual acuity have been reported. Studies have shown that retinal nerve fiber layer (RNFL) thickness measured by optical coherence tomography (OCT) is decreased in PD and some neurodegenerative diseases. Due to the similarities of ET and PD, we aimed to evaluate RNFL measured by OCT in ET and PD patients. Methods: PD, ET and control groups were formed in this prospective case-control study. Each group included 30 individuals, and 180 eyes were examined. In these groups, RNFL quadrants, macula and fovea were evaluated with OCT. In the ET group, tremor severity was included in the analyses. The severity of disease in PD was assessed with the Unified Parkinson’s Disease Rating scale and the Hoehn and Yahr scale. Results: In the control, ET and PD groups, the mean RNFL thicknesses of the right eye were 93.2 (8.1), 86.7 (9.7), 86.8 (10.2) μm, respectively. These values were lower in the PD and ET groups compared to the control group (P=0.026, P=0.025). There was no correlation between disease severity and RNFL thickness in ET. Conclusion: Decreased RNFL thickness in ET may indicate that ET is a neurodegenerative disease, such as PD. There may be subclinical retinal impairment in ET.